Construction of Information Sharing Incentive Model of Food Supply and Demand Network Based on Cross-chain - HE Jing; CAI Yong-qi; ZONG Chuan-hong (Liang you shipin ke-ji)
With the diversification of food varieties and the rise in consumer demands, food production processes have become more complex, and communication between supply chains has increased. The interactions among relevant enterprises, food supply chains, and industry institutions have formed a complex food supply-demand network structure. Information sharing among members of the food supply-demand network is beneficial for enterprises to fully cooperate and achieve long-term development. However, many enterprises still lack awareness of information sharing and are unable to communicate information effectively. The application and development of cross-chain technology in blockchain could provide a new perspective for information sharing in the food supply-demand network. According to the complexity of the food supply-demand network, blockchain technology and reputation incentive mechanisms have been introduced. Reputation was quantified and managed, and the reputation incentive mechanism was automated through the combination of blockchain smart contract technology. Furthermore, the introduction of blockchain cross-chain technology has broken down the transaction barriers between blockchains of different industries and regions, which could build an information-sharing reputation incentive model for the food supply-demand network based on blockchain cross-chain technology. The cross-chain information-sharing reputation incentive process was illustrated using the pork supply-demand network as an example. This incentive model not only ensured the security and accuracy of shared information but also protected enterprise privacy and maximizes the protection of the interests of transaction parties. It broke down the barriers that prevented information sharing, stimulating the enthusiasm of food supply-demand network enterprises to participate in information sharing. Not only does it has achieved information exchange and value interoperability between heterogeneous blockchains within the food supply-demand network, but it also has provided a new perspective for the development of value information exchange and interoperability in the food supply-demand network.